The School Environment and its Relation with the Quality of Teaching Physical Education - BENSABEUR, Mohamed; benkasdali, hadj mohamed; bensikaddour, habib; sebbane, mohamed; laroua, abdelhafid; BELKADI, Adel; benbernou, othmen; Gleyse, jaques (European Journal of Physical Education and Sport, www.ejournal7.com, 2015)
This study aims to explore the nature of the relationship between the quality of education of the PE and the school environment that revolves around the Sports and Physical Education lesson in high schools of the province of Mostaganem (Algeria). To achieve the objectives of this study, two questionnaires were designed. The first on the school environment and the second on the quality of education. A sample of 71 teachers spread across all high schools in the province of Mostaganem voluntarily took part in this study. The results showed a significant effect between the school environment and the quality of teaching physical education. This result allows to predict the quality of the teaching of physical education in high school requires a supportive school environment to meet the expectations and requirements of the discipline.
Keywords: school environment, quality of education, physical education